Образний простір амеріндіанських фольклорних текстів - Волкова, Світлана Володимирівна; Volkova, S. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті з етнолінгвістичної, лінгвокультурологічнї та когнітивно-семіотичної позицій досліджено образний простір амеріндіанських фольклорних текстів. Надано визначення міфолорним образам, представлено основні їх типи (образи-реалоніми, образи-артефакти, образи-символи), схарактеризовано їх функції в текстах. The article focuses on the problem of linguistic studying of image space in American Indians folklore texts. Ethnolinguistic, linguacultural and cognitive semiotic approaches have been applied in the research. As the factual material for investigation the identified problem we have taken Amerindian folk tales. Among the images of Amerindians folk tales there have been singled out images realonims, images artifacts and images symbols. It is proved that all of mentioned types of images comprise image space of folk tales and are of mythological and folklore nature. Due to this analyzed mages are identified as mytholoric. Mytholoric images are defined as the result of synthesized process of mixing the mythological and folklore features of the images with conceptualizing the ideas of Amerindian ethnos about making the world, the place of human being in it, nature phenomena, people and nature relationship. Analyzing the functions of mytholoric images in the texts highlighted their text forming, sense expressing and semiotic functions.
Amerindian folklore image space
Keywords: лінгвокультурологічний підхід; linguacultural approach; когнітивно-семіотичний підхід; cognitive semiotic approach; міфолорні образи; mytholoric images